Should all people starting urate-lowering therapy for gout receive anti-inflammatory prophylaxis? - Edward Roddy; James A. Prior; Christian D. Mallen (Exploration of Musculoskeletal Diseases)
Co-prescription of anti-inflammatory prophylaxis with colchicine, non-steroidal anti-inflammatory drugs (NSAIDs), or corticosteroids when initiating urate-lowering therapy (ULT) for gout is recommended in clinical guidelines to prevent ULT-induced flares and optimise adherence to ULT. Colchicine prophylaxis is highly clinically and cost-effective and there has been great interest recently in its cardioprotective effects. However, one in four people initiating ULT without prophylaxis in randomised trials do not have a gout flare within six months of initiation, raising the question of whether all people initiating ULT for gout should receive prophylaxis. Uptake of prophylaxis varies and appears to be common in secondary care settings but less commonly used in primary care, where most people with gout are managed and gout may be less severe. Recent clinical guidelines have highlighted that the patient’s perspective is important and that the pros and cons of prophylaxis should be discussed with people with gout initiating ULT. Uptake of prophylaxis seems likely to be influenced by perception of an individual’s risk of ULT-induced flares, as well as concerns about adverse events, polypharmacy, drug interactions, and cost. We advocate a personalised approach between people with gout and clinicians to reach shared treatment decisions when considering co-prescription of prophylaxis when initiating ULT, empowering people with gout to make decisions about their care.